NURSING CARE FACING THE NEEDS OF FAMILIES OF CHILDREN WITH DOWN SYNDROME - Rodrigues, Larissa (2022)
Objective: To understand the experience of nurses working in the Health Care Network in a city in the interior of São Paulo, with care for the health needs of families of children with DS. Method: This is a qualitative research supported by the methodological framework of Grounded Theory. Resulting from a covid-19 pandemic as identified, they were carried out online, considering theoretical saturation, with a total of 31 nurses from the hospital network and from the primary health care network in a city in the interior of São Paulo. Results: The categories included the experience of nurses in relation to their role in the process of child care and family assistance; in the assistance to children with DS in relation to their prior knowledge and difficulties in practice; as insecurities corresponding to the lack of knowledge during graduation and professional life, including prejudices and taboos in relation to DS in society. Conclusions: The study concludes that nursing care for families of children with Down syndrome is a care cycle, a child needs family support, the family needs professional encouragement and the nurse must be safe and qualified to contribute with guidance to family, showing how graduation and training opportunities during professional life can transform the care system.